(untitled) (Journal of Face Aesthetics, 2023)
Introduction. Needle mesotherapy is a procedure that has been known since the 20th century. It involves intradermal or subcutaneous administration of active substances that are responsible for renewal and regeneration. Cyclic punctures performed during the procedure further stimulate the formation of collagen, elastin and hyaluronic acid. Aim. The purpose of the study was to evaluate the effectiveness of needle mesotherapy treatment based on the subjective opinions of patients of aesthetic medicine offices in the Tri‑City area. Material and methods. Questionnaires of our own authorship were used in the study of patients’ opinions. The procedure was performed under local anesthesia, using a preparation containing in its composition hyaluronic acid and a mixture of amino acids. Results. Based on the obtained results, it can be concluded that needle mesotherapy treatment is a highly effective procedure that meets the expectations of clients. The main group of people interested in the treatment are women aged 40–45, with a college or post‑secondary education, living in a married couple. The effects of needle mesotherapy include an increase in hydration, improvement in firmness and elasticity, reduction of wrinkles, equalization of skin tone and increased skin smoothness. The increase in skin hydration and skin smoothness are the most visible effects. On average, 2 out of 10 needle mesotherapy treatments may be followed by side effects, which last up to a maximum of 3 days after treatment. Conclusions. Needle mesotherapy is one of the more popular and safe ways to preserve the youthful appearance of the face and neck skin. In the majority of treatments, side effects do not occur or are so minor that patients are able to return to daily life within a short period of time. The vast majority of respondents are satisfied with the results of the procedure performed and express a desire to continue.